Efektivitas Perencanaan Anggaran dan Koordinasi Terhadap Penyerapan Anggaran Belanja Pendidikan - Mahdi Mahdi; Fitriningsih Amalo; Supratman Supratman; Nunut Asniar; Bambang Surahman (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Education has a very important role in the development of a country, because quality education is the foundation of sustainable social and economic development. The aim is to analyze the effectiveness of budget planning and coordination on the absorption of the education expenditure budget. The research method used is a literature study or Library Research with a qualitative approach. Based on the literature review in this article, it can be concluded as follows (1) Budget planning affects the effectiveness of the absorption of the education expenditure budget. (2) Coordination affects the effectiveness of the absorption of the education expenditure budget. Keywords: budget planning, coordination, education spending budget